Tokamak research at the Ioffe Institute. (30th August 2019) - Bakharev, N.N.; Abdullina, G.I.; Afanasyev, V.I.; Altukhov, A.B.; Askinazi, L.G.; Babinov, N.A.; Bazhenov, A.N.; Belokurov, A.A.; Blekhshtein, M.D.; Bondarchuk, E.N.; Bukreev, I.M.; Bulanin, V.V.; et al.
Abstract: Recent research at three small tokamaks with different parameters located at the Ioffe Institute—the spherical tokamak Globus-M, the large aspect ratio tokamak FT-2 and the compact tokamak TUMAN-3M—are reviewed. This overview covers energy confinement (Globus-M and FT-2), L–H transition (TUMAN-3M and FT-2), Alfvén waves (Globus-M and TUMAN-3M), ion cyclotron emission (TUMAN-3M), major plasma discharge disruption (Globus-M) and scrape-off layer (Globus-M) studies. A full-f global gyrokinetic modeling benchmark using synthetic diagnostics in FT-2 is described. Anomalous absorption and emission in electron cyclotron resonance heating experiments due to the parametric excitation of localized upper hybrid waves are analyzed theoretically. Progress in the development of the neutral particle analysis, gamma-ray spectrometry and divertor Thomson scattering combined with laser-induced fluorescence diagnostics for ITER is discussed. The status of the new Globus-M2 spherical tokamak is reported.